QUALITY PROBLEMS IN EXPORTING KNITTED PRODUCTS - Sotvoldiyeva Nasibakhan (Journals Park Publishing, 2022)
This article is aimed at further increasing the export potential of the sewing and knitting industry produced in our republic .
Keywords: Export, Import, Customs, technical regulations, requirements.